EP-490 Management of femoral non-union with post-traumatic bone defect using second-generation PRECICE® nail - A Case Report. (9th August 2022) - Lu, Victor; Zhang, James; Krkovic, Matija
Abstract: Introduction: The management of post-traumatic bone defects with non-union remains a surgical challenge. Common limb length discrepancy (LLD) procedures involve Masquelet technique, vascularised bone grafts, distraction osteogenesis using external fixators, yet they pose a functional and economical challenge for patients, given high complication rates and need for revision surgery. Magnetically-driven PRECICE nails are self-lengthening internal devices activated via an external controller. We present one patient with post-traumatic femoral non-union with concomitant bone defect, using second-generation PRECICE nail. Case: One 57 year-old gentlemen suffered open femoral fracture after a motorcycle accident. Having previously undergone open reduction internal fixation, he presented to us with atrophic non-union and bone defect, which were simultaneously treated with a second-generation PRECICE nail. Our treatment protocol was based on the strain theory, and involved initial distraction by ∼5mm at non-union site, at a rate of 1mm per day, to decrease strain on bone graft cells and promote callus formation. One week later, the non-union site was compressed to close the gap completely. After another four weeks, distraction using the PRECICE nail started, in increments of 0.25mm, four times a day, until the desired length was achieved. The patient achieved union and the initially planned limb lengthening regime was achieved with minimal complications. Conclusions: By initially distracting the bone defect by ∼5mm, then compressing the gap, before distraction started, strain on bone graft cells was minimised, allowing robust callus and regenerate growth. Self-lengthening, magnetically-driven PRECICE nails can successfully restore union and manage limb length discrepancies with reasonable patient satisfaction and minimal complications.